Hadangan Games to Improve Gross Motor Skills in Elementary School Children - Bernhardin, DinDin; Ward, Ricky Ferrari Valentino; Alsyapari, Fahli (STKIP Paasundan Press, 2023)
This research aims to determine the impact of implementing the traditional game Hadangan in PJOK learning to improve the gross motor skills of elementary school children. This research is an experimental research method with a one group pretest posttest design. The research population was class V students at SDN Wiwitan, 31 students were used as research samples using total sampling techniques. The research instrument used was a motor ability test for children. The treatment was given 14 times, then the data was analyzed using the T-test in the SPSS version 25 application. The results of the research showed that the traditional game of hadangan had a significant impact on improving children's gross motor skills (Sig. 0.000). It can be concluded that traditional sports activities have very good potential in terms of improving children's gross motor skills.